Peripartum Ruptured Uterine Angioleiomyoma - Mohamed, Nora; Almasalma , Ayman (Gynecology Obstetrics & Reproductive Medicine, 2023)
Uterine angioleiomyoma is a rare entity. Angioleiomyoma is a benign vascular tumor that originates from the blood vessels. Although exceptionally they can be found in the uterus, they are commonly reported in the lower extremity. Preoperative diagnosis is tricky. We are publishing this case to highlight uterine contractions as a possible cause of the peripartum rupture. The patient was in her fourth pregnancy, with a history of three vaginal deliveries. She presented to the emergency department in our hospital with labor pain, at 39 weeks of gestation, and was admitted to the labor unit in active labor. She had an uneventful vaginal delivery with a good neonatal outcome. After delivery, the patient complained of abdominal pain, shoulder tip pain, and abdominal distention. Examination revealed a tender mass felt on the left side of the uterus up to the left hypochondriac region, contracted uterus, and normal lochia. A CT (computed tomography) scan was carried out and was remarkable for a left-sided, mixed-density, abdominopelvic lesion, measuring 18×12×9 cm, and a moderate amount of hemoperitoneum. Intraoperatively there was 1 liter of free blood, ruptured left-sided, subserous myoma connected to a 20×15 cm hematoma. A myomectomy was carried out. Histopathology reported an angioleiomyoma with symplastic-type cells. Although infrequent, complicated angioleomyoma should be suspected in the differential diagnosis of abdominopelvic hematoma in patients with uterine fibroids